Penskalaan Thurstone pada Aitem Thyroid Dysfunction Questionnaire (TDQ) Berbasis Gejala Biopsikososial - Mutalazimah, -; Azwar, Saifuddin; Murti, Bhisma (Jurnal Psikologi, 2014)
Thyroid function disorders can affect the biological, psychological and social conditions of the sufferer. This study aimed at developing a thyroid dysfunction questionnaire (TDQ) based on a biopsychosocial phenomenon, which is the impact of hypothyroidism and hyperthyroidism. The development of this instrument began with identification of the measurement objectives, domains and items. The procedures of Thurstone Scaling were done with analysis of content validity using the Content Validity Ratio (CVR) and Content Validity Index (CVI), which were formulated by three experts of thyroid and endocrinology. Every item in the TDQ was determined through median analysis based on the valuation results done by 44 internists from hospitals and 44 doctors from Puskesmas (Public Health Center) with 11 categories of response (1-11). The results of CVR analysis ranged from 0.33 to 1.00 and the value of CVI was 78%. It showed that the experts had adequate rate of homogeneity to judge the relevance of the 33 items in TDQ. The median analysis showed that the 33 items of TDQ had scores ranging from 4 to 10. Thus, it was expected that the TDQ scores on this interval scale would facilitate observer to make an interpretation of the examination of thyroid function of the subjects. Keywords: Thurstone scaling, thyroid dysfunction questionnaire, experts’ judgment, biopsychosocial